ANALYSIS OF EARNINGS QUALITY AND OPERATING EFFICIENCY OF SPECIFIC FINANCIAL INSTITUTIONS (SFLS) AND COMMERCIAL BANKS IN THAILAND - สมบัติชัย ภณิดา; สุทธิสานนท์ อภิรดา (RMUTT Global Business and Economics Review, 2016)
The purpose of this research study was to analyze the earnings quality and operating efficiency of the Specific Financial Institutions (SFIs) and commercial banks in Thailand. The study was conducted by analyzing information from financial statements since 2007-2011, annual reports, and other related documents from the samples of 6 SFIs and 14 commercial banks. Techniques used for the analysis of earnings quality included finding signals, evaluating the effects of accounting policy toward the quality of earnings, management appraisal, financial ratio analysis, cash flow ratio analysis, and measurement of the variation and the investment risk. Operating efficiency was measured by using financial ratios. Statistics used for the hypothesis testing was Paired Samples t-test. The results of the earnings quality analysis revealed that three techniques which positively affected the earnings quality consisted of evaluating the effects of accounting policy toward the quality of earnings, financial ratio analysis, and measurement of the variation and the investment risk. Meanwhile, the other three techniques which negatively affected the earnings quality included finding signals, management appraisal, and cash flow ratio analysis. Due to the analysis of efficiency, the results showed that the overall operating efficiency of the Banks was good indicating they were able to get cash from operation a lot comparing to revenues, interest and dividend, and asset investment. This was except some small and medium commercial banks whose efficiency tended to decrease. Besides, depreciation and amortization was good as an overall but appeared to decrease in terms of investment. Moreover, the earnings quality and the operating efficiency were significantly different depending on sizes of the commercial banks at a significant level of 0.05.